Echo intensity reliability between two rectus femoris probe sites. (November 2019) - Rabello, Rodrigo; Fröhlich, Matias; Bueno, Aline Felicio; Marcolino, Miriam Allein Zago; De Bona Bernardi, Thainá; Sbruzzi, Graciele; Aurélio Vaz, Marco
Introduction: The ultrasound technique has been extensively used to measure echo intensity, with the goal of measuring muscle quality, muscle damage, or to detect neuromuscular disorders. However, it is not clear how reliable the technique is when comparing different days, raters, and analysts, or if the reliability is affected by the muscle site where the image is obtained from. The goal of this study was to compare the intra-rater, inter-rater, and inter-analyst reliability of ultrasound measurements obtained from two different sites at the rectus femoris muscle. Methods: Muscle echo intensity was quantified from ultrasound images acquired at 50% [RF50 ] and at 70% [RF70 ] of the thigh length in 32 healthy subjects. Results: Echo intensity values were higher ( p = 0.0001) at RF50 (61.08 ± 12.04) compared to RF70 (57.32 ± 12.58). Reliability was high in both RF50 and RF70 for all comparisons: intra-rater (ICC = 0.89 and 0.94), inter-rater (ICC = 0.89 and 0.89), and inter-analyst (ICC = 0.98 and 0.99), respectively. However, there were differences ( p < 0.05) between raters and analysts when obtaining/analyzing echo intensity values in both rectus femoris sites. Conclusions: The differences in echo intensity values between positions suggest that rectus femoris's structure is not homogeneous, and therefore measurements from different muscle regions should not be used interchangeably. Both sites showed a high reliability, meaning that the measure is accurate if performed by the same experienced rater in different days, if performed by different experienced raters in the same day, and if analyzed by different well-trained analysts, regardless of the evaluated muscle site.